Effect of powdered milk containing Lactobacillus paracasei SD1 on salivary mutans streptococci and lactobacilli in orthodontic cleft patients - Chontira Saetang (Prince of Songkla University, 2014)
Thesis (M.Sc., Oral Health Science)--Prince of Songkla University, 2012